2017
DOI: 10.21608/adjg.2017.5199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatments on Cone Beam Computed Tomography Image and Push Out Bond Strength of Conventional and Reinforced Fiber Posts.

Abstract: Statement of problem:Surface treatment of reinforced fiber posts may not always increase adhesion, especially on post/resin based luting agent interface which is weaker than the dentin/adhesive interface. Relatively little information is available on cone beam computed tomography as non-destructive method suitable for investigating the details of the tooth structure and restoration relationship. Purpose: The purpose of this study was performed to evaluate porosities and gaps at post/ root dentin interface by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Regarding the influence of surface treatments on the glass fiber posts, These findings of the current study exhibited significant improvement in pushout bond strength values after being treated with 9.5% Hydrofluoric acid etching followed by silane application more than other glass fiber post groups. (28) , Mazzitelli, et al(2008) (29) , Mohsen C (2012) (1) , Abd El Wahab& El-Sharkawy (2017) (10) and Alshahrani, et al(2021) (30) found that, The use of silane after etching with 9.5% hydrofluoric acid produced excellent results for the push out bond strength of glass fiber posts.…”
Section: Dupagne Et Al (2023)mentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the influence of surface treatments on the glass fiber posts, These findings of the current study exhibited significant improvement in pushout bond strength values after being treated with 9.5% Hydrofluoric acid etching followed by silane application more than other glass fiber post groups. (28) , Mazzitelli, et al(2008) (29) , Mohsen C (2012) (1) , Abd El Wahab& El-Sharkawy (2017) (10) and Alshahrani, et al(2021) (30) found that, The use of silane after etching with 9.5% hydrofluoric acid produced excellent results for the push out bond strength of glass fiber posts.…”
Section: Dupagne Et Al (2023)mentioning
confidence: 98%
“…Next, the posts were coated using a disposable brush with silane coupling agent (BISCO porcelain primer , USA), and left to air dry for five minutes. (1,10)…”
Section: (B) Construction Of Peek Post (Custom Made)mentioning
confidence: 99%
See 1 more Smart Citation